Acute psychosis in elderly: do not forget the CASPR2 spectrum as a possible cause - André Ricardo Merkle; Marco Antônio Machado Schlindwein; Letícia Caroline Breis; Marcus Vinícius Magno Gonçalves (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2020)
Antibodies against contactin-associated protein 2 (CASPR2), a protein associated with the Voltage-Gated Potassium Channel Complex (VGKC) [1], represent an emerging cause of some old neurological manifestations; such as Morvan's and Isaacs' syndromes, as well as a variety of phenotypes encompassing limbic encephalitis, neuropathic pain, late onset epilepsy and dysautonomia [2,3].